2012
DOI: 10.1016/s1473-3099(12)70121-4
|View full text |Cite|
|
Sign up to set email alerts
|

Estimated global mortality associated with the first 12 months of 2009 pandemic influenza A H1N1 virus circulation: a modelling study

Abstract: None.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
827
2
22

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,119 publications
(902 citation statements)
references
References 43 publications
17
827
2
22
Order By: Relevance
“…Age‐specific cumulative incidence rates are critical parameters used by public health decision makers and mathematical modelers in planning for and responding to a pandemic and provide accurate denominator estimates to calculate a key parameter – the case fatality ratio. Together with recent1 and forthcoming2 estimates of H1N1pdm mortality – the numerator of the case fatality ratio (CFR) – and our summary cumulative incidence results, we suggest that the CFR of the pandemic virus was approximately 0·02% providing insight into the severity of the 2009 influenza pandemic globally.…”
Section: Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…Age‐specific cumulative incidence rates are critical parameters used by public health decision makers and mathematical modelers in planning for and responding to a pandemic and provide accurate denominator estimates to calculate a key parameter – the case fatality ratio. Together with recent1 and forthcoming2 estimates of H1N1pdm mortality – the numerator of the case fatality ratio (CFR) – and our summary cumulative incidence results, we suggest that the CFR of the pandemic virus was approximately 0·02% providing insight into the severity of the 2009 influenza pandemic globally.…”
Section: Introductionsupporting
confidence: 66%
“…This consistency in estimated infection rates by age group between countries may have been strengthened in part because we consistently categorized our sera based on timing of collection in relation to peak H1N1pdm viral activity in each country. Assuming that the cumulative incidence in the countries included in our studies is similar to the rest of the world for which no little data exist and if the global mortality estimates produced by two research groups1, 2 are confirmed by other studies, this would place the CFR for H1N1pdm at <0·02%.…”
Section: Discussionmentioning
confidence: 73%
“…In addition, HIV‐positive South Africans have been shown to be at greater risk for severe influenza illness 6. The high prevalence of underlying high‐risk medical conditions, including HIV and tuberculosis, likely contributes to higher influenza‐associated mortality in South Africa 7, 8…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, few estimates are available about the economic impact‐related caregivers' lost productivity and money spent on over‐the‐counter medications and other out‐of‐pocket expenses. Last, most data are from high‐income countries, despite the fact that influenza occurs in low‐ and middle‐income countries at similar or greater rates 5, 6, 7. To assess the full economic burden of influenza in a middle‐income country, we estimated both the direct and indirect costs among persons enrolled in a community‐based cohort study of influenza in Peru.…”
Section: Introductionmentioning
confidence: 99%